Analysis of the Relationship between Economic Growth and Environmental Health Quality on the Island of Java - Rahmawati, Oktaviani Laila Nur; Suryanto, Suryanto; Suryantoro, Agustinus (Integrated Journal of Business and Economics (IJBE), 2024)
This study aims to find out the impact of the indicators of the index of quality of living environment, investment, and access to health services on economic growth in the island of Java in the year 2017-2021. The study uses secondary data and methods of analysis of data regression panel with the method of the approach Fixed Effect Model Results in the study show that the Index of Water Quality, Air Quality Index , and Investment have a significant influence on economic considerations, However, the Index Of Quality of Land Coverage and Access to Health Services has no significant drivers to economic growth. In this study, there are limitations in obtaining samples of data that are respective and unbiased.This study suggests that increased economic growth can deteriorate the quality of health. This is especially true in the context of less visionary environmental policies.